Karakter Fenotip Malai dan Analisis Fenetik Padi Gogo Lokal Kabupaten Kupang - Hanas, Dicky Frengky; Palege, Jeremy Jethro (Program Studi Biologi, Universitas Timor, 2023)
Panicle is one part of the plant that is very decisive in rice production because it produces grain and rice grains. Each rice variety has its own characteristics including panicle morphological characters. Communities in Kupang Regency are known to still cultivate local upland rice whose panicle character has not been scientifically documented. This study used 5 varieties of local upland rice as a result of exploration from farmers in Kupang Regency which were characterized morphologically by their panicle characters. Characterization data were analyzed using descriptive qualitative and then scored for analysis using Minitab17 software. The results showed that there was a diversity of panicle morphological characters from each local upland rice variety. The differentiating panicle characters of each variety include panicle type, panicle discharge, secondary panicle branches and panicle shaft. The phenetic analysis divided the five local upland rice varieties into two clusters with a similarity index of 79.94%.